Budaya Batimbang pada Bayi yang Lahir Dibulan Safar pada Masyarakat Sangasanga - Yohana Mega Nanda; Lilik Andaryuni; Ashar Pagala (Bulletin of Community Engagement, 2024)
In ancient times, the Jahiliyah Arab community believed in the month of Safar as a month that brought bad luck. But not all people believe in this. Because there are so many traditions that are often carried out by many groups to welcome the month of Safar, one of them is to do Betanding for newborn babies. The purpose of this study is to find out how the cultural development contained in the Batanding tradition is in the Banjar community who live in Sangasanga District. The factors that underlie some Banjar people believe in and carry out certain practices in the month of Safar based on information from the books of previous scholars submitted by religious leaders so that a process of suggestion and imitation of behavior occurs (modelling). This tradition has been passed down from generation to generation until now. The motivation and goal is to gain safety and avoid bad luck.